How to build houses and save the countryside - Spiers, Shaun (Policy Press shorts. Insights., 2018)
England has a housing crisis. We need to build many more new homes to house our growing population, but house building is controversial, particularly when it involves the loss of countryside. Addressing both sides of this critical debate, Shaun Spiers argues that to drive house building on the scale needed, government must strike a contract with civil society: in return for public support and acceptance of the loss of some countryside, it must guarantee high quality, affordable developments, in the right locations. Simply imposing development, as recent governments of all political persuasions have attempted, will not work. Focusing on house building and conservation politics in England, Spiers uses his considerable experience and extensive research to demonstrate why the current model doesn't work, and why there needs to be both planning reform and a more active role for the state, including local government--